PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT DINAMIKA LOGAMU MULIA - Safika, Nurul; Syaifullah, Syaifullah (SCIENTIA JOURNAL, 2021)
Given that importance of human resources in the development and progress of a company, companies should consider human resources more than just company assets but as partners in business. As a partner in business, the company must be fair for what human resources have given to the company. This aims of studies were determining the effect of compensation and motivation on employee performance at PT Dinamika Logamu Mulia. The designs of that studies using a researches designed and quantitatives causality research methods. The results of this study indicate that compensation (X1), and motivation (X2) have a partial, simultaneous effect. and significant on employee performance (Y). The results of the determination coefficient test show that compensation (X1) and motivation (X2) are 79.4 percent, while the remaining 20.6 percent is influenced by other variables not examined in this study. Keywords: Compensation; Employee Performance; and Motivation.